(untitled) (Journal of Energy and Safety Technology (JEST), 2023)
Oil and gas are common fossil fuels consumed as a source of power, causing irreparable damage such as acid rain, greenhouse gas emissions, environmental pollution and climate change. The importance of preserving the environment and the nature of fossil fuels have drawn much attention from many to implement renewable sources. With that, wind turbine implementation has shown a competitive advantage because they are a reliable source of energy, sustainable, and environmentally friendly. However, the wind turbines implementation potentially poses challenges in services, cost, and others. This paper establishes an influencing factor in wind turbine implementation at the existing building site in ensuring the project’s success and minimizing the risk. This paper uses the questionnaire survey directly distributed to the green building certified facilitators, and government and private organisations experts in renewable energy implementation. Factor Analysis has been conducted as an analysis method of data reduction based on Principal Component Analysis with Varimax Rotation. The prioritization of factors was summarized based on the factor loading threshold 0.50 and above. The Factor Analysis results revealed that the Management, Environmental, Economic, Design and Site Assessment Factor achieved a significant loading value. This paper provides information about the influencing factors that require consideration when implementing the wind turbine to achieve an optimal strategy.